3d-4-5d=7+d

Simple and best practice solution for 3d-4-5d=7+d equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3d-4-5d=7+d equation:


Simplifying
3d + -4 + -5d = 7 + d

Reorder the terms:
-4 + 3d + -5d = 7 + d

Combine like terms: 3d + -5d = -2d
-4 + -2d = 7 + d

Solving
-4 + -2d = 7 + d

Solving for variable 'd'.

Move all terms containing d to the left, all other terms to the right.

Add '-1d' to each side of the equation.
-4 + -2d + -1d = 7 + d + -1d

Combine like terms: -2d + -1d = -3d
-4 + -3d = 7 + d + -1d

Combine like terms: d + -1d = 0
-4 + -3d = 7 + 0
-4 + -3d = 7

Add '4' to each side of the equation.
-4 + 4 + -3d = 7 + 4

Combine like terms: -4 + 4 = 0
0 + -3d = 7 + 4
-3d = 7 + 4

Combine like terms: 7 + 4 = 11
-3d = 11

Divide each side by '-3'.
d = -3.666666667

Simplifying
d = -3.666666667

See similar equations:

| 8(3x+2)-4x=6 | | 8x+42b+544z=1000 | | 8x+2y=242 | | (2,8)5/2= | | 3a-(4b+2a)+5b= | | 3x^5-12x^4-45x^3+180x^2-48x+192=0 | | A=sw+w*w | | 5x-7+3x=7x-10 | | 5j+10=5 | | (9x^2+8x-2)+(-5x^2-7x+3)= | | 10x-5=12+6x | | P+0.02p=142.8 | | 25(xsqured-9)=25(x-3)(x+3) | | 8(3n+5)=8(9n+9)+6 | | In(x)=20 | | x+x*0.14=500 | | C=a+(n-8)dforn | | -6x-1=-6 | | 42/0.5= | | 2a+7=5a+9 | | 10r^2-2r=-4r+6 | | (x-6)*(x-6)=(x*x)-396 | | 45=2y | | 5x+43-2(x+7)=88-2x | | 0.16(y-2)+0.12y=0.20y-0.7 | | x^2-17X+3=0 | | 5x+43-2(x-7)=88-2x | | 8x^4+10x^3-14x^2-4x=0 | | 6x-3x=4x-1 | | y=4xn | | 2x^2-196-70x=0 | | 2y=.5x+6 |

Equations solver categories